Solidification of electroplating sludge with alkali-activated fly ash to prepare a non-burnt brick and its risk assessment. Issue 8 (29th January 2020) - Xia, Ming; Muhammad, Faheem; Li, Shan; Lin, Huirong; Huang, Xiao; Jiao, Binquan; Li, Dongwei
Abstract : Electroplating sludge was solidified in alkali activated fly ash to prepare non-burnt bricks, and their risk to humans was assessed. Abstract : Electroplating sludge (ES), a byproduct of the electroplating industry, is considered as hazardous waste because of the presence of several kinds of toxic heavy metals (HMs, i.e., Cr, Ni, Cu and Zn). The improper treatment of ES has resulted in the contamination of the environment and is ultimately harmful to the living biota. Solidification/stabilization is regarded as a promising technique to deal with hazardous wastes with the use of a geopolymer, an excellent material, in this technique. In this research, ES was solidified using fly ash (FA) and ordinary Portland cement together so that non-burnt bricks (NBBs) could be prepared. The risk assessment of these bricks was carried out in a homemade experimental device by simulating rainfall. The results showed that the compressive strength of NBBs was up to 15 MPa; hence, it could be used for construction purposes. The hazard quotient (HQ) of HMs (including Zn, Ni and Cu) was much less than the limit value, while both the HQ and cancer risk of Cr were over the corresponding limit values.